The rise of microcredit 'control fraud' in post-apartheid South Africa: from state-enforced to market-driven exploitation of the black community. Issue 161 (3rd July 2019) - Bateman, Milford
ABSTRACT: The end of apartheid in South Africa in the early 1990s did not see the envisaged end to the exploitation of the black South African population, but instead saw simply a shift from state-backed exploitation to market-driven exploitation. This trajectory is especially germane to the country's microcredit industry, which has spectacularly and wilfully enriched a narrow white male elite while simultaneously helping to fragment and destroy the local rural and urban economies of the black poor. As this article demonstrates, a major aspect of this one-sided enrichment process has involved 'control fraud', the process whereby the CEO and senior management of a financial institution use their seniority to defraud customers, shareholders, the government and the general public as they go about maximising their own private short-term financial gains. Already a problem elsewhere in the global South, South Africa has thus joined the growing list of countries that have seen control fraud in the microcredit sector undermine and block progress towards more productive, sustainable and equitable local economies.